Proposed Maintenance Policy Design on Paving Molding Machine Using Reliability and Risk Centered Maintenance (RRCM) Method at PT XYZ - I Gede Oka Mahendra; Fransiskus Tatas Dwi Atmaji; Judi Alhilman (OPSI, 2021)
PT. XYZ is a company engaged in construction and manufacturing. The company focuses on paving production. Where there is a problem with paving printing machines in carrying out production, there are many productions that do not reach the target or the production process does not run optimally.   The purpose of this study is to find out the performance of paving molding machines, especially in the components that most often experience damage to paving molding machines. Based on historical data on machine damage, a paving molding machine is a machine that has had the highest frequency of damage for 5 years, because this machine operates continuously to meet production targets and paving demand from customers. Reliability and Risk Centered Maintenance (RRCM) methods to be used to analyze a historical engine malfunction. The results obtained in the form of 7 proposed maintenance tasks are 2 scheduled on-condition tasks, 3 scheduled restoration tasks, 2 scheduled waste tasks. In addition, the average maintenance time interval for pillow blocks is 7 months, iron molding is 11 months, and chain is 4 months. The total cost of proposed maintenance is lower than IDR 52,938,750 or 41.7% compared to the existing maintenance cost of PT. XYZ. The development of this research is to increase the application of RCM as a basis for maintaining the balance between preventive maintenance and corrective maintenance while optimizing maintenance costs to improve engine reliability by considering risk factors as an analysis.